Sleep, Sloth, and Sanctification - McMartin, Jason (Journal of spiritual formation & soul care, 2013)
I develop a spiritual theology of the physical act of sleep. The spiritual significance of the physical act of sleep ought to be a relational trust that recognizes my place as a creature that depends on the grace of a self-sufficient provider. After distinguishing this topic from other related themes, I develop a theological anthropology of sleep by considering how sleep brings glory to God and by placing sleep within the redemption narrative. I explore sleep as a spiritual practice and investigate the theme of sleep as trust in Scripture. I exposit a spiritual danger associated with sleep, the capital vice of sloth, and show how the traditional conception of this vice further illumines the spiritual significance of sleep.